2022
DOI: 10.3390/ph15010061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MDI Actuation Timing on Inhalation Dosimetry in a Human Respiratory Tract Model

Abstract: Accurate knowledge of the delivery of locally acting drug products, such as metered-dose inhaler (MDI) formulations, to large and small airways is essential to develop reliable in vitro/in vivo correlations (IVIVCs). However, challenges exist in modeling MDI delivery, due to the highly transient multiscale spray formation, the large variability in actuation–inhalation coordination, and the complex lung networks. The objective of this study was to develop/validate a computational MDI-releasing-delivery model an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…These included: (1) different inhalation conditions (transient vs. constant), and (2) the accuracy of modeling spray properties. The mean diameter of 16.54 µm and an initial speed of 100-120 m/s were used for discharged Ventolin sprays [14], which are significantly higher than the mean diameter of 9.1 µm measured by Liu et al [20], and the initial velocity of 40 m/s predicted by Talaat et al [19]. The mouth-throat models in Biswas et al [8] and Yousefi et al [14] are also different, even though they may not be significant contributors to their observed differences.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These included: (1) different inhalation conditions (transient vs. constant), and (2) the accuracy of modeling spray properties. The mean diameter of 16.54 µm and an initial speed of 100-120 m/s were used for discharged Ventolin sprays [14], which are significantly higher than the mean diameter of 9.1 µm measured by Liu et al [20], and the initial velocity of 40 m/s predicted by Talaat et al [19]. The mouth-throat models in Biswas et al [8] and Yousefi et al [14] are also different, even though they may not be significant contributors to their observed differences.…”
Section: Discussionmentioning
confidence: 74%
“…The airway model extended from the mouth-opening to lung bronchioles of the ninth generation of bifurcations (i.e., G9). This model was developed in our previous studies, with detailed procedures reported in [17][18][19]. The shape of the mouth opening was adapted to connect snuggly with the inhaler mouthpiece.…”
Section: Mdi-airway Geometrymentioning
confidence: 99%
“…Pressurized metered-dose inhalers (pMDIs) are sturdy containers that hold medication dissolved or dispersed in liquefied propellants. Device actuation–patient inspiration, i.e., device–patient coordination results in precise inhalation dosimetry [ 218 ]. The propellants rapidly evaporate due to their high vapor pressure, allowing the patient to breathe in the aerosolized medication particles.…”
Section: Pulmonary Drug Deliverymentioning
confidence: 99%
“…Our geometries, including a cylinder representing the open-air environment, two nozzle geometries, and the real MT model, were discretized using tetrahedral elements in ANSYS® Workbench. The prism elements with eight layers of thickness and a transition ratio of 0.272 were generated in the region near the airway wall to capture the high gradients near the walls (Feng et al 2021;Talaat et al 2022). The geometries and mesh were imported into ANSYS Fluent 2020R2 (ANSYS, Inc).…”
Section: Mesh Generationmentioning
confidence: 99%
“…Plume properties also change when inhalation flow is used, compared to no-flow conditions (Moraga-Espinoza et al 2018). Talaat et al (2022) recently suggested that a study on plume behaviour should be done under close to real conditions during drug delivery, but this is currently not experimentally feasible.…”
Section: Introductionmentioning
confidence: 99%